1978
DOI: 10.1037/0022-006x.46.6.1192
|View full text |Cite
|
Sign up to set email alerts
|

Internal–external expectancies and health-related behaviors.

Abstract: The present article is a review of research on internal-external (I-E) locus of control expectancies and health attitudes and behaviors. The theoretical background of the I-E construct is described. Topics covered include I-E in relation to health knowledge, precautionary health practices, reactions to physical disorders, psychological responding, psychological disturbances, and responses to psychological treatment. Some problems and issues are also noted.Health concerns and health costs constitute a social pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
195
0
10

Year Published

1981
1981
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 402 publications
(212 citation statements)
references
References 101 publications
7
195
0
10
Order By: Relevance
“…The term locus of control refers to the site of a cause, that is, whether or not the outcome of an event is attributed to something inside (internal to) or outside (external to) the person involved (Rotter, 1954(Rotter, , 1966Strickland, 1978;Tones, 1997;Weiner, 1986). Locus of control relates to people's attitudes, emotions, health, and motivation, as well as behavior in organizations and educational institutions (Spector and Fox, 2005).…”
Section: Levels Of Locus Of Control and Academic Attitudes Among Univmentioning
confidence: 99%
“…The term locus of control refers to the site of a cause, that is, whether or not the outcome of an event is attributed to something inside (internal to) or outside (external to) the person involved (Rotter, 1954(Rotter, , 1966Strickland, 1978;Tones, 1997;Weiner, 1986). Locus of control relates to people's attitudes, emotions, health, and motivation, as well as behavior in organizations and educational institutions (Spector and Fox, 2005).…”
Section: Levels Of Locus Of Control and Academic Attitudes Among Univmentioning
confidence: 99%
“…En general una atribución interna producirá una mayor actividad y persistencia en el afrontamiento que una atribución externa. Según ha sido informado por Strickland 20 , en la atribución interna predominan las estrategias dirigidas al problema, por el contrario, si la atribución es externa predominan las estrategias que son dirigidas a la emoción.…”
Section: Atribuciones De Controlunclassified
“…Previous studies found that high self-efficacy and internal LoC are related to resilience in both mental and physical health outcomes (Strickland, 1978;Strecher et al, 1986;Weiss and Larsen, 1990;Bandura, 1993;Wu et al, 2004;Shelley and Pakenham, 2004;Zajacova et al, 2005;Marks et al, 2005;Cross et al, 2006;Leontopoulou, 2006;Cohen et al, 2008;Waldron et al, 2010;Craig et al, 2011;Oliveira et al, 2012). Specifically in regard to PTSD, self-efficacy and LoC are significantly associated with individual differences in pathology and posttraumatic recovery Heinrichs et al, 2005;Chung et al, 2006Chung et al, , 2007Chung et al, , 2012Jones et al, 2006;Mak et al, 2010).…”
Section: Introductionmentioning
confidence: 99%